Effects of the reduction of caffeine consumption on tinnitus perception - Figueiredo,Ricardo Rodrigues (2014)
INTRODUCTION: For many years, excessive caffeine consumption has been touted as an aggravating factor for tinnitus. The pathophysiology behind this effect is probably related to the blockage of adenosine receptors by the action of caffeine on the central nervous system. OBJECTIVE: To evaluate the effects of reduction of coffee consumption on tinnitus sensation and to identify subgroups more prone to benefit from this therapeutic strategy. Study design: prospective. METHODS: Twenty-six tinnitus patients who consumed at least 150 mL of coffee per day were selected. All were asked to reduce their coffee consumption. The Tinnitus Handicap Inventory (THI) questionnaire was completed by the patients before and after the reduction of coffee consumption, as well as a visual-analogue scale (VAS) graduated from 1 to 10. RESULTS: THI and VAS scores were significantly reduced (p < 0.05). In the subgroups less than 60 years old, bilateral tinnitus and daily coffee consumption between 150 and 300 mL showed a significantly greater reduction of THI and VAS scores. CONCLUSION: Patients under 60 years of age with bilateral tinnitus and daily coffee consumption between 150 and 300 mL are more prone to benefit from consumption reduction. Thirty-day observation periods may be helpful for a better therapeutical decision.